Factors facilitating and hindering South Asian immigrant adults from engaging in exercise and physical activity - a qualitative systematic review - Nasimah Maricar; Behram Khan; Trixy David; Kimme L Hyrich; Anne Barton (BMC, 2024)
Abstract Background Exercise and physical activity are key components of management in patients with rheumatic musculoskeletal diseases (RMD), but people of the South Asian communities have a lower level of engagement with these activities compared to their Caucasian counterparts. The aim of this qualitative systematic review was to determine the barriers and facilitators of exercise and physical activity in South Asian communities who have migrated and live in western countries, particularly in those who have RMD. Methods Qualitative studies, published in English between 1999 and 2021 and including evaluation of barriers and/or facilitators to exercise or physical activity behaviour in people of South Asian adult communities who have migrated and/or lived in western countries were identified from Embase, MEDLINE, CINAHL, PsycINFO, Google Scholar and manual searches. The studies were appraised using the CASP checklist. Inductive thematic synthesis was used to identify common and global themes. Results A total of 32 studies that discussed barriers and facilitators of physical activity in South Asian communities who have migrated and lived in western countries were used for this review but there were no studies identified that focussed specifically on those with RMD. Following appraisal of the reporting of the studies, 30 studies were included in the pooling of the results. The facilitators and barriers to physical activities were broadly categorized into 'extrinsic' and 'intrinsic' factors. Extrinsic factors such as 'opportunity' included environmental factors such as weather and safety; socioeconomic factors such as education, language and literacy, and support in the form of social, psychological and resources. Intrinsic factors included cultural factors, such as life stages and family influence, beliefs and knowledge, which impacted attitudes and skills. Conclusions This review has synthesised evidence of barriers or facilitators and identified potentially modifiable factors influencing physical activity and exercise engagement, which could form the basis of evidence-based interventions to promote participation in healthy behaviour change. Provision of a safe, comfortable and culturally acceptable environment together with culturally-aligned cognitive strategies to facilitate acquisition of exercise-efficacy skills could help engagement. Registration The systematic review was registered on PROSPERO, registration no. 289,235.